CO2 methanation over Ni/Al hydrotalcite-derived catalyst: Experimental characterization and kinetic study. (1st August 2018) - Marocco, Paolo; Morosanu, Eduard Alexandru; Giglio, Emanuele; Ferrero, Domenico; Mebrahtu, Chalachew; Lanzini, Andrea; Abate, Salvatore; Bensaid, Samir; Perathoner, Siglinda; Santarelli, Massimo; Pirone, Raffaele; Centi, Gabriele
Graphical abstract: Highlights: Ni/Al hydrotalcite-derived catalyst testing at 1 atm and 270–390 °C. Good catalyst stability over time. Investigation of intrinsic kinetics of CO2 methanation. Developing of power law, power law with inhibition and LH rate equations. Abstract: The catalytic performance of a Ni/Al hydrotalcite derived catalyst for CO2 methanation was analysed under different operating conditions. The as synthesized sample has been characterized through atomic adsorption spectroscopy (AAS) X-ray diffraction (XRD), Brunauer-Emmett-Teller (BET) analysis, temperature programmed reduction (TPR) and CO chemisorption. Experimental investigation was carried out at atmospheric pressure by varying the reactor bed temperature (within the range 270–390 °C), the H2 /CO2 feed ratio and the reactant flow rate. The impact of methanation products on the reaction rate was also analysed by co-feeding reactants with steam and methane. Stability tests were also performed, showing a good catalytic performance of the hydrotalcite-derived catalyst over time. Different kinetic rate expressions were then developed starting from experimental results. Power law, power law with an inhibition term and Langmuir-Hinshelwood (LH) approach were tested and compared. The methanation reaction was first modelled by considering the Sabatier reaction. Then, the reverse water-gas shift (RWGS) was also added to account for the presence/formation of CO. A nonlinear regression analysis was performed with the aim of finding kinetic parameters values allowing the minimization of the discrepancy between measured and calculated values of the CH4 yield (or CO2 conversion). Results showed a better fitting of experimental data by using the LH expression and the power law (with inhibition influence of adsorbed water or hydroxyl). Main transport criteria were finally checked to evaluate whether operating conditions have been chosen properly in order to study the intrinsic reaction kinetics.